Studying the co-reaction of propenyl-substituted cyanate ester-bismaleimide blends using model compounds - Hamerton, I.; Howlin, B.J.; Jewell, S.L.; Patel, P. (Reactive & functional polymers, 2012)
Reactive modifiers, bearing cyanate and/or alkenyl groups have been shown to improve the thermo-mechanical and water uptake properties of cured bismaleimides and BMI/cyanate ester blends. The allyl-substituted modifiers have been the subject of much study, but the reaction mechanism of the more reactive propenyl analogues (for which lower moisture absorptions have been recorded) have not received much attention until the present study. The synthesis and full characterisation of model maleimide and propenyl-substituted aryl cyanate compounds is reported. Infrared and Raman spectroscopy and thermal analysis techniques are used to examine the thermally initiated co-reaction between blends of the two model compounds. Raman spectroscopy reveals that as the thermal reaction proceeds, there is a pronounced decrease in the alkenyl CC stretch band at 1655cm−1 as a function of temperature and this is accompanied by a concomitant decrease in the vinylidene band at 3010cm−1. In the absence of a dedicated catalyst, the cyanate cyclotrimerization is slow and follows the co-reaction between the alkenyl group and the maleimide ring. Molecular modelling experiments using semi-empirical and ab initio methods support the formation of the trans ene adduct which is consistent with calculated and observed vibrational frequencies.